(untitled) (Journal of the Sylhet Agricultural University, 2025)
The study was aimed to analyse the marketing channels, intermediary involvement, their roles in fish marketing, and associated costs throughout the movement of fish in Bagerhat, Bangladesh. Specifically, the investigation focused on the marketing channels and value chain of commercially significant marine fish, particularly sea bass (Lates calcarifer), in Bagerhat area. Questionnaire survey method was used for the data collection and relevant information of this research. It was observed that intermediaries collectively yield significant profits, resulting in higher fish prices in the consumer market. The marketing margin for sea bass was calculated at 26%, with fishermen receiving 74%, 80%, and 90% of the consumer purchase price in the primary, secondary, and retail markets, respectively. In the local sea bass market, five intermediaries were involved (sea bass farmer, aratdar, wholesaler, retailer, and consumers), while in distant markets included four intermediaries in total marketing channel (sea bass farmer, wholesalers, retailers, and consumers). The major challenges in the marketing channel are inadequate infrastructure, transportation amenities, and a significant number of intermediaries for the commercially important marine fishes. To establish a sustainable fish marketing system, requires the organizational support, government assistance, extension services, and training opportunities for market operators. J. Sylhet Agril. Univ. 11(1): 01-08, 2024